Delivery, barriers, and enablers to patient participation in inpatient cardiac rehabilitation following cardiac surgery: An integrative review. Issue 3 (May 2023) - Nasrawi, Dima; Latimer, Sharon; Massey, Debbie; Gillespie, Brigid M.
Abstract: Background: Cardiovascular disease is the leading cause of death worldwide. Cardiac surgery is the main treatment followed by inpatient cardiac rehabilitation (ICR) to prepare patients for recovery. Aim: The aim of this study was to describe the delivery, barriers, and enablers to patient participation in ICR programs after cardiac surgery. Methods: This integrative review was guided by Whittemore and Knafl's methodology. This process included database searches, data evaluation, data integration, and presentation of results. Searched databases included Medline, CINAHL Complete, PsycINFO, Cochrane Library, and Web of Science. Publications dates included 2000 to 2021. Studies included Phase 1/inpatient phase cardiac rehabilitation following cardiac surgery. The Mixed Method Appraisal Tool (2018) was used to assess the quality of the included studies. Inductive content analysis was used to analyse the textual data. Results: Using the inclusion and the exclusion criteria, 607 articles were screened. Five articles were included in this review, and they were appraised. Categories comprised of the following: i) ICR programs using a multidisciplinary approach beginning in the early postoperative stage; ii) ICR programs including multicomponents that were delivered through an individualised approach; and iii) enablers and barriers to patient participation to ICR. The enablers included religious faith and family support, whereas inconsistent pathways of cardiac rehabilitation referrals and detachment from patients' experiences and needs were barriers to participation in ICR. Conclusions: In some instances, ICR programs were delivered using individualised approaches, but this is an area that needs improvement. A multidisciplinary team including nurses should be involved in the ICR phase after cardiac surgery to provide holistic care and enhance patients' preparedness to participate in subsequent phases of rehabilitation. Only five relevant articles addressing the delivery of inpatient cardiac rehabilitation were identified in this specific topic area.